Investigating gender differences in mathematics by performance levels in the Italian school system. (September 2021) - Matteucci, Mariagiulia; Mignani, Stefania
Highlights: Gender gap in mathematics of Italian students is investigated by performance levels. Comparing the overall performance, boys outperform girls already at primary school. The quantile regression analysis shows different gaps depending on the score levels. The impact of gender is different on the three main latent performance classes. In the highest scholastic grades, most differences are at the intermediate levels. Abstract: Amongst the extensive research conducted about girls' lack of interest in STEM subjects, an issue that is frequently examined is the learning of mathematics. This research investigates the gender gap in mathematics among Italian students based on performance levels, using standardised large-scale data from INVALSI tests. We performed a quantile regression to better understand the differences along the entire score distribution. A latent class model was then estimated to identify groups of students with similar performance levels, taking into account the gender covariate. The results indicate that boys are already ahead from primary education and that there is a general decrease in the performance as students progress through the education stages.